Living and Learning at the Intersections of Identity and Community: Facilitating Theatre of the Oppressed Workshops with Educators. Issue 4 (2nd October 2019) - Foster-Shaner, Liz; Sondel, Beth; Generett, Gretchen; King, Michelle
Abstract: For the past year, we have been co-facilitating Theatre of the Oppressed (TO) workshops across Pittsburgh, tailored specifically toward local educators and educational activists. The overarching intentions of these workshops were twofold: (a) to cultivate educators' understanding of and response to how power and privilege operate in educational systems; and (b) to provide useful tools for educators to continue these conversations and dismantle systems of oppression in their places of practice. As a collective of facilitators and in our workshops, we attempt to create, even if briefly, a beloved community where participants are invited to bring their full, human selves and engage in nuanced reflection in the hopes of creating a more compassionate, just, and equitable society. Like our workshops, the purpose of this article is both practical and theoretical: (a) to provide tangible tools to those readers interested in facilitating TO workshops for educators; and (b) to contribute to our understanding of how TO can serve to cultivate educators' analysis of oppression.